Generic green skills: maturity level of vocational education teachers and students in Indonesia - Mutohhari, Farid; Sudira, Putu; Pardjono, Pardjono; Suyitno, Suyitno; Warju, Warju; Isnantyo, Fajar Danur; Majid, Nuur Wachid Abdul (International Journal of Evaluation and Research in Education (IJERE), 2025)
Vocational education (VE) is one of the institutions that must answer environmental problems by providing green job skills to its students. However, VE in Indonesia still experience various obstacles in providing this provision, so the aim of this research aims to analyze the extent of the level of green skills (GS) in teachers and students in this country, which includes the dimensions of cognitive, interpersonal and intrapersonal competence as an illustration for developing a priority scale for improvement. In addition, examining the differences and correlations between dimensions and the contribution of dimensions to GS as a whole is an additional goal. The survey method was carried out using a generic GS questionnaire instrument in VE that have Adiwiyata status. Data were analyzed using three stages: descriptive analysis, ANOVA-post hoc Tukey test, and path analysis. As a result, students’ GS still show a low category, while teachers get a high category. Between dimensions show no significant differences. Finally, all competencies have a significant relationship and can construct overall GS. These results indicate that there is still a need to strengthen teacher competencies in GS-based learning management and strengthen collaboration with all levels of society.